Latitudinal clines in the grasshopper Dichroplus elongatus: Coevolution of the A genome and B chromosomes? - Rosetti, Maria Eva Natalia (2013)
Argentine populations of Dichroplus elongatus (Orthoptera: Acrididae) are polymorphic for B chromosomes. Previous studies showed that B chromosomes affect body size and some fitness components in Northwestern populations. We studied phenotype and B′s variation patterns along a latitudinal cline as well as the relationship between karyotype and body size related traits in 17 populations from East.Body size related traits showed a ‘saw tooth’ pattern of variation being small at low and high latitudes and large at intermediate latitudes in most of the analysed populations. Analyses of variance and principal components demonstrated that in most analysed populations B carrier males are associated with a decrease in body size related traits with respect to individuals with standard karyotype. Accordingly with the relationship between karyotype and body size, an opposite pattern of latitudinal variation in the frequencies of B′s with respect to body size variation was observed in this area. i.e. smaller individuals tend to have a higher frequency of B chromosomes. The comparison of the differentiation of both karyotype and body size traits with molecular neutral markers demonstrated the relative importance of selection moulding chromosome and phenotype variation. The observed pattern of phenotypic variation is likely to be the result of local adaptation to season length along the latitudinal gradient. The observed contrary pattern of B′s clinal variation may reflect the population ability to maintain this chromosome in relation to the local adaptation. The available evidence indicates that the distribution of B chromosome frequency was shaped by selective factors.